Effect of guava leaf and lemon extracts on postharvest quality and shelf life of banana cv. Sabri (Musa sapientum L.): Effect of plant extract on banana shelf life (Journal of the Bangladesh Agricultural University, 2018)
Banana is a common and popular subtropical fruit worldwide. Its postharvest life is very short which causes difficulties in marketing and preserving banana at good condition. To find out a better solution of this problem, the current study was conducted during 2017 in the Horticulture Laboratory, Khulna University, Bangladesh, by following the Completely Randomized Design (CRD) of experiment. Harvested banana fruits, sabri (Musa sapientum L) were treated with guava leaf and lemon extracts at different concentrations. Non-treated fruits were considered as control. Both treated and non-treated bananas were stored in covered paper carton at ambient condition. Postharvest performances of the stored fruits during storage were observed for two weeks. After two weeks of storage, lower changes in color (score 6.77), firmness (score 4.43), less TSS content (8.21%), minimum infection (48.89%) and disease severity (score 3.33) and maximum shelf life (8.75 days) were observed in banana fruit with treatment of T3 (guava leaf extract 20% + lemon extract 15%) followed by treatment of T5 (guava leaf extract 40% + lemon extract 15%) treated fruits. However, the T4 treated banana fruit showed maximum vitamin C (1.83 mg/100 g), titratable acidity (0.11%) and reduced sugar (7.13%) after two weeks of storage. In conclusion, combination of guava leaf extract (20% or 40%) + lemon extract (15%) could be suggested for long term storage and maintenance of postharvest qualities at ambient conditions.J. Bangladesh Agril. Univ. 16(3): 337–342, December 2018